INTERNATIONAL COMMUNITY SERVICE: EMPOWERING EARLY CHILDHOOD THROUGH BOARD GAMES TO ENHANCE SELF-CARE SKILLS AT THE INDONESIAN SCHOOL OF KUALA LUMPUR (SIKL), MALAYSIA - Jhoni Warmansyah; Elis Komalasari; Wahidah Fitriani; Afriyane Ismandela; Dinda Fatma Nabila; Dola Permata Sari; Rupinis, Rupinis (Perkumpulan Pendidikan Islam Anak Usia Dini Wilayah Sumatera, 2024)
The International Community Service program aimed to empower early childhood education by training kindergarten teachers at Sekolah Indonesia Kuala Lumpur (SIKL), Malaysia, to design board games that enhance self-care skills in young children. This program utilized a participatory action research (PAR) approach, engaging 20 teachers through workshops and mentoring sessions. The results revealed a significant improvement in the teachers' ability to create interactive and engaging learning activities, with self-care concepts successfully integrated into the board games. The games were well-received by students, enhancing their motivation and engagement in practicing self-care routines. These findings emphasize the effectiveness of game-based learning in teaching essential life skills. It is recommended to continue the training sessions and expand collaboration with other educational institutions to ensure lasting impact